Optimum planting ratio and staggered sowing of male parent for DHB-290 (inter-specific) cotton hybrid seed production - S.R. DODDAGOUDAR; M. SHEKHARGOUDA; B.M. KHADI; M.R. ESHANNA; N.K. BIRADARPATIL; S.N. VASUDEVAN (Seed Research, 2026)
Continuous pollen availability and synchronous flowering determines the success of cotton hybrid seed production. The planting ratio of 2:1 (Female: male) and staggered sowing of male (25% each) one week before, along with one and two weeks after female parent sowing was found to be optimum to get better synchronization in female and male parents by efficient utilization of male flowers and to obtain higher hybrid seed yield with better quality.